2003
DOI: 10.1080/17461390300073105
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a recreational exercise program with differentiated frequency on functional capacity and daily activities patterns in older women

Abstract: The purpose of this study was, first, to evaluate the effects of a 12-week recreational exercise program on the level of physical abilities and on the level of daily activities of 55 sedentary elderly women, aged 60 to 75, and second, to examine the minimal amount of exercise needed to produce these changes. The variables used to test the functional capacity were dynamic balance, muscular endurance, sit and reach flexibility, and muscular coordination. The variables that tested the daily physical activity (ADL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The significant proportion of time children spend at school makes schoolyards a critical determinant for motivating students into a more active lifestyle (Erwin et al, 2012). The ecological model maintains that the natural environment along with intra-personal, inter-personal and socio-cultural factors influences PA at behavioural level (Bebetsos and Goulimaris, 2014;Haug et al, 2010;Matsouka et al, 2003aMatsouka et al, , 2003bNaylor and McKay, 2009;Sallis et al, 2006). Therefore, the outdoor school setting can encourage students' PA so that daily required PA levels are met.…”
Section: Introductionmentioning
confidence: 99%
“…The significant proportion of time children spend at school makes schoolyards a critical determinant for motivating students into a more active lifestyle (Erwin et al, 2012). The ecological model maintains that the natural environment along with intra-personal, inter-personal and socio-cultural factors influences PA at behavioural level (Bebetsos and Goulimaris, 2014;Haug et al, 2010;Matsouka et al, 2003aMatsouka et al, , 2003bNaylor and McKay, 2009;Sallis et al, 2006). Therefore, the outdoor school setting can encourage students' PA so that daily required PA levels are met.…”
Section: Introductionmentioning
confidence: 99%
“…Most exercise noncompliance occurred with participants missing 1–2 days of exercises and re-initiating the exercises as prescribed. Although little research has investigated the effect of exercise frequency on the efficacy, previous studies have shown that exercising as little as twice a week can improve flexibility, and exercising as little as twice a week can improve strength [51]. Similarly, it has been shown that hand strength programs offer similar benefits in elderly participants when completed daily or when completed every other day [52].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that this amount is satisfactory for the maintenance of independence 20,21 and is sufficient to improve dynamic balance, strength and muscular coordination in sedentary elderly women. 22 The muscle groups were chosen because of their importance in functional activities. 13,23 The muscle groups were trained with Cybex seated_leg_press and seated_hip_abduction training devices (CY-BEX International Inc., Medway, MA, USA).…”
Section: Strength Trainingmentioning
confidence: 99%